Implementation of Management Information System Website-Based Letter Archives - Budi Mukhamad Mulyo (Fakultas Teknik Universitas Bhayangkara, 2021)
The development of an institution currently requires Information Technology, at the level of commercial institutions and non-commercial institutions. The development of this technology is expected to support ongoing work so that it is easier and more systematic. One technology that is often used is the Management Information System. With this Management Information System Technology, it is hoped that users can store data easily and access it again quickly. In this study, the author tries to implement a Correspondence Management Information System with a case study at the Faculty of Informatics Engineering at Bhayangkara University Surabaya. This information system includes incoming and outgoing letters, with several supporting tools so that it can handle scanned and input data manually.